2016
DOI: 10.1177/0271678x16676825
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive near-infrared fluorescence imaging of the neutrophil response in a mouse model of transient cerebral ischaemia

Abstract: Near-infrared fluorescence (NIRF) imaging enables non-invasive monitoring of molecular and cellular processes in live animals. Here we demonstrate the suitability of NIRF imaging to investigate the neutrophil response in the brain after transient middle cerebral artery occlusion (tMCAO). We established procedures for ex vivo fluorescent labelling of neutrophils without affecting their activation status. Adoptive transfer of labelled neutrophils in C57BL/6 mice before surgery resulted in higher fluorescence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Neutrophils were isolated from the bone marrow of C57BL/6 mice and labeled for nearinfrared fluorescence (NIRF) imaging as previously described [29,30]. Isolated neutrophils were incubated in HBSS (0.2x10 6…”
Section: Adoptive Transfer Of Fluorescent-labeled Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils were isolated from the bone marrow of C57BL/6 mice and labeled for nearinfrared fluorescence (NIRF) imaging as previously described [29,30]. Isolated neutrophils were incubated in HBSS (0.2x10 6…”
Section: Adoptive Transfer Of Fluorescent-labeled Neutrophilsmentioning
confidence: 99%
“…We first asked if absence of ICAM-1 reduced the accumulation of CD45 + /Ly6G + neutrophils following tMCAO and reperfusion. We have previously shown that near-infrared fluorescence (NIRF) imaging provides a versatile tool to non-invasively study dynamics of neutrophil accumulation into the mouse brain after experimental cerebral ischemia [30]. Taking (Fig.…”
Section: Absence Of Icam-1 Does Not Affect Neutrophil Accumulation Inmentioning
confidence: 99%
“…For granulocyte labeling, nanoparticles must have appropriate physicochemical properties in relation to size, coating, zeta potential, concentration and stability; these proprieties contribute to efficient internalization, maintaining the cell viability of the granulocytes [75][76][77]. Efficient labeling with the contrast agent is important in granulocyte detection by different imaging techniques supporting various clinical applications, such as immune response, diagnosis and therapies [51,[78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…However, this view has been challenged by a number of other studies 5 , 6 , 10 , 21 and later, also, a partly revised view of the original authors appeared. 7 …”
Section: Role Of Polymorphonuclear Neutrophils For Ischemic Reperfusimentioning
confidence: 99%
“…Postischemic neuroinflammation comprises the early (within minutes to hours poststroke) infiltration of the injured brain by polymorphonuclear neutrophils (PMNs) and monocytes/macrophages. 5 7 This is accompanied by the activation of microglia and expression of proinflammatory cytokines, adhesion molecules and integrins, which are supposed to contribute to ischemic reperfusion injury. 5 , 8 , 9 Massive infiltration of PMNs into ischemic brain tissue has recently been documented in human stroke patients.…”
Section: Introductionmentioning
confidence: 99%